Psikoedukasi Psikologi Positif: Sebuah Intervensi “Grit” pada Siswa SMA X di Tangerang - Marganel, Brendha; Ilyas, Putri Ardhiyyah Muammar; Justine, Leticia; Hidayat, Ivana Tatiana; Khong, Zorryhazel; Novanto, Yusak (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The transition period from high school to university level is a critical time for individual development among students, particularly to begin the emerging adulthood period. The aim of implementing the Grit Up! 2024 is to measure the effectiveness of the